MODINET: Challenges and Archievements - Skogerbø, Eli (MedieKultur: Journal of media and communication research, 2006)
The article reviews the achievements of MODINET by commenting on the Center's publications, approaches and methods. Dividing the publications into three broad themes - democracy studies, journalism studies and studies of interfaces - the article discusses the Center's findings and results against an international research agenda.